The Effect of the Cooperative Model of Teams Games Tournament (TGT) Assisted by Wordwall Media on Improving the Initial Reading Ability of Elementary School Students - Adya Pramudya Dwi Permata Radianty; Indah Nurmahanani; Nadia Tiara Antik Sari (Al-Madrasah: Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2026)
This study was motivated by the low reading skills of lower grade students, characterized by difficulties in recognizing letters, reading syllables, and reading comprehension. This study aims to determine the effect and improvement of the Teams Games Tournament (TGT) learning model assisted by wordwall media on improving students' reading skills. The study used a quasi-experimental method with a Nonquivalent Control Group Design. There were 58 first-grade students participating in the study, divided into class I A with 28 students as the experimental class and class I B with 30 students as the control class. The instrument used was the EGRA test. Data analysis included normality and homogeneity tests, N-Gain calculations, and T-tests. The results showed that the experimental class experienced an increase in early reading skills with an average N-Gain of 0.65, higher than the control class at 0.31. In addition, the T-test results showed a sig value < 0.05, which means there was a significant difference between the two classes. Thus, the TGT learning model assisted by wordwall media is effective in improving the early reading skills of first-grade students.